Multifunctional hearing aids (Aideway) / Aqilah Hanan Mohd Jalani … [et al.] - Mohd Jalani, Aqilah Hanan; Zainudin, Auni Syazwin; Hanafi, Nur Syahirah; Mohd Reduan, Nurul Syazwani Natasya; Mohd Shah, Sufi Sufiya (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
AIDEWAY or Multifunctional Hearing Aids is an ultra-modern hearing device that has been developed in accordance with this increasingly advanced technological world. This hearing aid is created with the intention of guiding individuals with hearing impairments with their auditory experiences. This multi use hearing aid is focusing on these three functions. First and foremost, the Danger Detector Function. This functionality will be Bluetooth-connected to their cars, and we hope it can help the users to stay alert about dangers that might occur such as car accidents. The second function that we formed is On Call Function. Users can use this device to communicate with others through phone calls without having to remove the device from their ear. With a little touch, the users can connect their incoming calls from their mobile phone to their hearing aids. Aside from that, this device also provides a noise cancellation function. This function will benefit the users as they can’t hear outside voices or sounds when they are on call. Last but not least, is Adjusted Volume Function. This function is provided to assist the users to listen to the speakers more clearly. This inventive device potentially can help individuals with hearing impairments to go through their daily lives smoothly. Our hope is that these hearing problem individuals do not feel burdened for lacking in one of the most essential body functions, and we do wish that they also can live their life happily as much as other normal people in this beautiful world.